Contributing factors of Islamic banks profitability in Malaysia / Siti Nur Alyaa Izzati Shaikh Rahim ... [et al.] - Shaikh Rahim, Siti Nur Alyaa Izzati; Md Nor, Nor Haryanti; Mohd Aznan, Nadia Farleena; Nik Muhammad Naziman, Yusrina Hayati; Abdul Rahman, Siti Maziah; Yaacob @ Othman, Azmahani (2021)
Malaysia has been prosperous in implementing dual banking systems in attracting more depositors. The concept of dual banking systems became more prudent to the markets internationally. As bank profitability is one of the main factors of a stable banking system, many theoretical and empirical studies have tried to identify the determinants of bank profitability. This study was conducted to discover the relationship between fundamental strength across Islamic banks laterally return on asset with the bank size, capital adequacy and liquidity to Malaysian Islamic banks profitability. A sample size consisting of 5 years of yearly data has been gathered and summarized for 10 Malaysian Islamic Banks from 2013 until 2017. The data were then analyzed using STATA 12, specifically Pooled Ordinary Least Squares method, Random Effect Model and Fixed Effect Model. It was revealed that only liquidity is significant in determining profitability while bank size and capital adequacy are insignificantly related. According to the Panel Pooled (OLS) method, there is a significant relationship between liquidity and return on asset of Malaysian Islamic banks. The remaining independent variables, bank size and capital adequacy, are not significant but positively influence the return on asset. The result suggests that liquidity is significantly correlated to all profitability measures and hence requires some modification by management to spur back an accurate conclusion in terms of deposits ROI. The Islamic banks perhaps work in a similar direction with conventional banks in conjunction with the better economic-financial evolution, and their profits need to be secured and elaborated.